Clinical usefulness of repeated sputum culture for the identification of pneumonia pathogens: A retrospective study - Ji Hyun Yun; Jiho Park; Hyun Kyun Ki (PLoS ONE, 2026)
Sputum culture is essential for identifying pneumonia pathogens, but its sensitivity remains limited. This study evaluated the clinical utility of repeated sputum cultures and factors associated with detecting additional significant isolates in subsequent cultures. We retrospectively analyzed adult patients with pneumonia who underwent three serial sputum cultures at a tertiary hospital between January 2021 and December 2022. We excluded patients with over 48 h interval between each sputum sample or those with coronavirus disease 2019. Initial and subsequent culture results were compared, and clinical factors associated with detecting additional significant isolates were evaluated. A total of 132 patients were included. Sputum quality (p = 0.71) and culture positivity rates (p = 0.25) were similar across serial cultures. Fungi, particularly Candida species, were more frequently isolated from subsequent cultures (p = 0.02). The cumulative detection rate of significant isolates did not improve, although the cumulative number was higher in third than initial cultures (p = 0.01). Hypertension, inappropriate empirical antibiotics, shorter intervals to repeat culture, and greater pneumonia severity were independent risk factors for detecting additional significant isolates. Serial sputum cultures provided limited additional diagnostic information and were not associated with meaningful improvement in the sputum quality, culture positivity, or cumulative detection of significant isolates.